Esensi dan Kearipan Budaya Lokal: Tradisi Hari Raya Ngubur Masyarakat Desa Sungai Gelam Kabupaten Muaro Jambi di Era Revolusi 4.0 - Amir Syarifuddin; Relawati Relawati (Jurnal Siginjai, 2021)
The current era of globalization is certainly a lot of changes in all fields. Especially in the field of science and technology. Science continues to develop rapidly technology is growing rapidly as well. Along with the rapid development of this technology, it also has an impact on everyday life. Where people's lives must also follow the development of technology as it is today. Like wise with culture, as science and technology advances, local cultures must be able to balance or adapt to the times. However, along with the development of technology as it is today, the people of Sungai Gelam Village still maintain their habits or traditions. The tradition of burying this day is a tradition carried out by the people of Sungai Gelam Village during the Eid al-Fitr holiday. The people of Sungai Gelam village continue to carry out the Ngubur Hari Raya Tradition because they think that this tradition must be preserved because according to them itcontains a lot of religious elements as well as to connect the ties of friendship between extended families. The development of the times in the Industrial Revolution era had no effect on the people of Sungai Gelam Village. For them, times may change, but their ancestral culturemust be preserved and will not be timeless.